Extreme call amplitude from near-field acoustic wave coupling in the stridulating water insect Micronecta scholtzi (Micronectinae). Issue 138 (31st January 2018) - Reid, Andrew; Hardie, David J. W.; Mackie, David; Jackson, Joseph C.; Windmill, James F. C.
Abstract : Underwater acoustic transducers, particularly at low frequencies, are beset by problems of scale and inefficiency due to the large wavelengths of sound in water. In insect mating calls, a high call volume is usually desirable, increasing the range of signal transmission and providing a form of advertisement of the signaller's quality to a potential mate; however, the strength of the call is constrained by body size and by the need to avoid predators who may be listening in. Male crickets and water boatmen avoid some of the limitations of body size by exploiting resonant structures, which produce sharply tuned species-specific songs, but call frequency and volume remain linked to body size. Recently, the water boatman Micronecta scholtzi was found to circumvent this rule, producing a louder mating call than that of similar, but much larger, Corixa . The resonant structure in Corixidae and Micronectinae is believed to be the trapped air reserves around the insect as it dives, driven by a stridulatory apparatus. However, the method by which energy is transferred from the striated area to the bubble is unknown. Here, we present modelling of a system of near-field coupling of acoustic sources to bubbles showing an exponential increase in sound power gain with decreasing distance that provides a simple solution to the stimulus of the air bubbles in Corixidae and Micronectinae and explains the discrepancy of M. scholtzi 's extreme call volume. The findings suggest a possible route to engineered systems using near-field coupling to overcome size constraints in low-frequency (less than 500 Hz) underwater transducers, where the input efficiency of a piezoelectric device can be coupled through the hydrodynamic field to the high radiative efficiency of a near-ideal monopole emitter.